Nilai Pendidikan Karakter dalam Kumpulan Dongeng Masyarakat Mandar Karya Syuman Saeha dan Hendra Djafar - Amini A, Nurul Azisyah; Sulastriningsih, Sulastriningsih; Saleh, Muhammad (Fakultas Teknik Universitas Negeri Makassar, 2024)
This research aims to describe nationalist values in the book Cerita dari Bumi Tipalayo (Collection of Fairy Tales) by Syuman Saeha and Hendra Djafar This research uses a type of qualitative research using a descriptive approach. The data collection technique used was reading and recording. The collected data were analysed including stages: data identification, data classification, data analysis, data description, and data interpretation. The results showed that there were 5 sub-values of nationalist character found in 10 stories in the story book from Bumi Tipalayo by Syuman Saeha and Hendra Djafard found. These sub-values are: respecting differences by prioritising tolerance, preserving the nation's cultural wealth, appreciating.